Tourist Object in Tomohon City as a Basic Consideration for Tourism Destination Development in Highland Ecosystem - Henny Johanna Kambey (Program Pascasarjana, 2016)
Tourism potential attraction identification is the crucial aspect in tourism destination planning and development. Tomohon in North Sulawesi rich in term of tourism attraction, but tourism development is limited. Based on the tourism potential identification, Tomohon has numerous natural and potential attractions. The highland environments of Tomohon contributes significantly in natural tourism object. Tourism potential distributes in all area of Tomohon city with north Tomohon as centre of tourism destination. Natural resources of Tomohon should be managed in sustainable manner following sustainable principles.Keywords: mountain tourism, tourism data, agrotourism, sustainable tourism.Â